Mapping redistribution in terms of family: A European comparison. (May 2023) - Frericks, Patricia; Gurín, Martin; Höppner, Julia
Redistribution is one of the fundamental characteristics of developed societies. While societal redistribution between working and non-working citizens has been studied intensively, redistribution in terms of family has been analysed mainly as private redistribution. In this contribution, we study societal redistribution in terms of family by systematically analysing its regulation and simulating its results. We map family-related redistribution in Europe by analysing to whom financial resources are granted (benefits) and from whom resources are demanded (obligations) to identify the degree and logic of family-related redistribution. We compare 68 family forms in 27 European countries based on the micro-simulation model EUROMOD. The findings show that there are clear country-clusters of redistribution in terms of family. They differ, though, as to benefits and obligations. The degree of redistribution reveals that in most countries, societal redistribution is highest towards low-income, single-parent families and lowest towards low-income family forms without children.